Community Rituals in Facing Volcanic Eruption Threat in Java - Permana, Septian Aji; Liernoor, Dewi; Slamet, Achmad; Juhadi, Juhadi (Universitas Negeri Semarang, 2017)
This research aims to explore the kinds of rituals done by the society in around Merapi mountain facing volcanic mountain eruption threat in Cangkringan and find educational meaning in the ritual. This research uses qualitative approach, phenomenology. Research informants are Cangkringan society, Merapi mountain caretaker, and Cangkringan figures.Â Data collecting technique are participant observation; the researcher involved directly in the ritual. Data then analyzed by using domain, taxonomic, componential, and cultural theme. Research result shows that Cangkringan society in facing Merapi mountain eruption threat is still traditionally by labuhan ritual , laku topo bisu ritual, and sedekah Gunung ritual. These rituals are representation of educational values and local wisdom whose most fundamental objectives are to maintain nature, the values of togetherness, in order and respect to achieve outer and inner harmony.